PENGELOLAAN PEMBELAJARAN BERBASIS PENDEKATAN BEYOND CENTERS AND CIRCLE TIME (BCCT) PADA ANAK PLAYGROUP DI SEKOLAH ALAM BOSOWA - Nurrahmatillah Nurrahmatillah; Arifuddin Siraj; A. Nur Maulana (Idaarah: Jurnal Manajemen Pendidikan, 2019)
This research  aims to  know learning  management in the early childhood  Bosowa Alam school with the BCCT approach. The previous main problem to be   listed  into a number of subproblems, namely 1) What kind of learning resources used in early childhood in the Bosowa Alam school? 2) How to manage learning toward early childhood education at Bosowa Nature School by applying BCCT and DAP? This research classified as qualitative with employing  pedagogical and psychological approach. The data was taken from head master, class Guardian, Teachers and students. The data collection methods used observation, interviews, documentation, and some  referencea. Techniques of data analysis carried out in three stages, namely data reduction, data presentation and conclusion collection. The results of this study indicate the fact that several things must be highly considered by educators before formulating a learning plan that will be used in early childhood of bosowa natural school. The implementation of learning supported by learning resources used in each center to be developed with 5 child domains (affection, language, cognition, social and psychomotor) and 7 multiple intelligences (logical-mathematical intelligence, Sapatial intelligence, musical intelligence, kinesthetic intelligence, Interpersonal and Intrapersonal intelligence). The management of Bosowa Alam school learning resources carried out in 5 stages: students identification, planning learning resources, preparing learning resources, using learning resources as well and evaluation methods.